Optimal Bone Preparation for Triple-Tapered Stems: Does the Sagittal Taper Affect Optimal Femoral Sizing? - Jeff Shi, MD; Kevin Salomon, MD; Victor Shen, BS; Andrew Moore, MD; John T. Wilson, MD; Brian Palumbo, MD (Arthroplasty Today)
Background: Conventional single-tapered, total hip arthroplasty stems achieve fixation namely through coronal, metaphyseal fit. Triple taper stems have a sagittal taper to optimize fixation in the antero-posterior (AP) plane as well; however, limited guidance exists on appropriate bone preparation. Often, similar preparation techniques are used despite geometric differences which may lead to underpreparation. We’ve defined a novel technique in which a small portion of posterior femoral neck and cancellous bone is removed to permit preparation collinear to the diaphyseal sagittal femoral axis. We hypothesize this will optimize stem fit and stability compared to conventional techniques. Methods: This is a retrospective review of 38 cementless primary total hip arthroplasty cases performed by a single surgeon. In each case, broach preparation was initially performed through the center of the femoral neck as although it was a single-tapered stem. Once tactile sensation of adequate fit was achieved, fluoroscopic images were taken to document AP and mediolateral fit, and stem size was recorded. Then that broach was removed, and a standardized one-third of the posterior femoral neck and posterior cancellous bone was removed, permitting broaches to prepare the femur collinear to the femoral diaphyseal sagittal axis— triple-tapered preparation (TTP). Outcomes included change in stem size from initial broach trial to final stem selection and radiographic stem fill on AP and lateral views. Results: Median single-tapered preparation broach size was 8 (range, 5-12) and final stem size after TTP was 11 (range, 6-13). The TTP overall mean percent metaphyseal fill was 74 ± 6% in the AP view and 71 ± 5% in the lateral view, both significantly higher than single-tapered preparation which was 67 ± 7% and 65 ± 7%, respectively (P < .001). No fractures or loosening occurred in this series. Conclusions: Preparation of triple-tapered stems collinear to the diaphyseal sagittal femoral axis improves stem size, fit, and fill.